الرسوم والعمولات المصرفية وأثرها على الإيرادات الصافية في المصارف التجارية التقليدية العاملة في سورية - العمار رضوان; عبيده هبه (Latakia University Journal - Economic and Legal Sciences Series, 2018)
فرضت ثورة التكنولوجيا وتحرير الخدمات المالية تحديات صعبة على المصارف, دفعتها إلى تنويع مصادر إيراداتها وذلك بتطوير وتحديث خدماتها, للحصول على دخل متمثل بالرسوم والعمولات المصرفية, ومن هذا المنطلق هدف هذا البحث إلى دراسة أثر الرسوم والعمولات المصرفية التي تتحملها وتتقاضاها المصارف التجارية التقليدية العاملة في سورية، على إيراداتها الصافية. اعتمدت الباحثة على البرنامج الإحصائي Eviews5, وحللت بيانات بانل التي تم الحصول عليها من التقارير السنوية للمصارف التجارية التقليدية عينة الدراسة والعاملة في سورية, وذلك عن الفترة الممتدة من عام 2009 وحتى عام 2014, باستخدام كل من نموذج الأثر الثابت ونموذج الأثر العشوائي ثم أجرت اختبار هوسمان لاختيار النموذج الأنسب للدراسة. ومن أهم الاستنتاجات التي تم التوصل إليها أنَّ كلاً من الرسوم والعمولات المصرفية الدائنة والمدينة, تؤثر إيجابياً على الإيرادات الصافية للمصارف التجارية التقليدية العاملة في سورية، وأوصت الباحثة أن تعمل هذه المصارف على تطوير وتحديث خدماتها, بشكل يزيد من دخل الرسوم والعمولات المصرفية لديها, وبالتالي يزيد من إيراداتها الصافية. The revolution of technology and the liberalization of financial services, imposed tough challenges to banks, pushed to diversify its sources of revenue by developing and upgrading its services, to get represented income of bank fees and commissions, and from this perspective the goal of this research is to study the impact of banking fees and commissions incurred by and charged by traditional commercial banks operating in Syria, on net revenues. Researcher relied on Eviews5 statistical program, and analyzed Panel data that have been obtained from the annual reports of traditional commercial banks of the study sample and operating in Syria, and that for the period from 2009 to 2014, using both fixed-effects model and random-effects model and then conducted a Hausman test to choose the most appropriate model for the study. One of the main conclusions that have been reached, that both bank fees and commissions payable and receivable, positively affect the net revenues of traditional commercial banks operating in Syria. The researcher recommended these banks to work on the development and modernization of its services, in order to achieve more banking fees and commissions income, thus increasing its net revenues.